PENGARUH NILAI PELANGGAN YANG DITAWARKAN SEKOLAH UNGGULAN NURUL ISLAMI SEMARANG TERHADAP KEPUASAN SISWA - Bagus Yunianto Wibowo; Mudiantono Mudiantono (JURNAL STUDI MANAJEMEN ORGANISASI, 2014)
The research has the efforts of junior high school, high school and vocational school inUnggulan Nurul Islami (Nuris) Semarang, to become the institution that not only deliverswhat the needs of the students, but is also able to offer values that can satisfy the students.This research identified at least 4 (four) the troubles in this research besides found theproblem in service quality, human resources quality, and location of Unggulan NurulIslami Semarang. The research also get a referral earlier research that deserves to beresearched further in an upcoming research. Therefore, the formulation of the problem inthe research is how to increase student satisfaction in accordance with the expectationsof the school through the value of the customer. This research also formulate models and4 (four) research hypothesis.This research uses a sample of 100 students in junior high school, high school andvocational school Nuris Semarang. In this research using of intervening models (multipleregression analysis) and survey methods with questionnaires. Primary Data is requiredand tested is the quality of human resources, the quality of the education service,location, customer value offered and satisfaction of students.The results of this research demonstrating that the model and the four (4) hypothesisreceived significantly. And the research found that the quality of human resources (HR) isthe most dominant variables that affect student satisfaction through customer value.Therefore, it can be concluded to improve the quality of human resources at the juniorhigh school, high school and vocational school became the main determinant in studentsatisfaction through customer value at Unggulan Nurul Islami Semarang.Keywords: Human Resources Quality, Service Quality Education, Location, CustomerValue Offered, and Student Satisfaction